1955
DOI: 10.1071/bi9550288
|View full text |Cite
|
Sign up to set email alerts
|

The Bilateral Structure of Wool Cortex and Its Relation to Crimp

Abstract: Xew evidence of the nature of the bilateral cortex in crimped wool is presented and discussed in relation to the physical and chemical properties of the wool fibre. The origin of the asymmetry in the cortex was studied by cutting cross sections of sheep skin and swelling plucked wool roots.It is shown that the bilateral structure is present before the cortex is keratinized and does not originate from an asymmetrical keratinization as has been suggested. Coarse wools, in which crimp is much less, are shown to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1958
1958
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…Remarkably, there is insufficient human hair structural biology information known to provide a fundamental understanding of hair curvature. In contrast, substantial progress in sheep wool fiber structural biology (Rogers, 1959a,b;Bradbury, 1973;Kaplin and Whiteley, 1978;Orwin, 1979a,b;Marshall et al, 1991;Bryson et al, 2001;Caldwell et al, 2005a,b) reveals a strong correlation between the lateral distributions and abundances of para-, meso-, and orthocortical cell types and single fiber curvature (Horio and Kondo, 1953;Fraser and Rogers, 1955;Whiteley and Kaplin, 1977;Kaplin and Whiteley, 1978) and fiber diameter (Orwin and Woods, 1980;Orwin et al, 1984). Transmission electron microscopy (TEM) has revealed that cortical cell types are differentiated by morphological and/or structural variations in distinct subcellular components, namely: the intermacrofibrillar material (IMM), the cytoplasmic remnants (CR), the macrofibrils (Mfs), and the Mf components: the intermediate filaments (IFs) or trichocyte (hard a-keratin) proteins, embedded in a matrix material composed of keratin associated proteins (KAPs).…”
Section: Introductionmentioning
confidence: 88%
“…Remarkably, there is insufficient human hair structural biology information known to provide a fundamental understanding of hair curvature. In contrast, substantial progress in sheep wool fiber structural biology (Rogers, 1959a,b;Bradbury, 1973;Kaplin and Whiteley, 1978;Orwin, 1979a,b;Marshall et al, 1991;Bryson et al, 2001;Caldwell et al, 2005a,b) reveals a strong correlation between the lateral distributions and abundances of para-, meso-, and orthocortical cell types and single fiber curvature (Horio and Kondo, 1953;Fraser and Rogers, 1955;Whiteley and Kaplin, 1977;Kaplin and Whiteley, 1978) and fiber diameter (Orwin and Woods, 1980;Orwin et al, 1984). Transmission electron microscopy (TEM) has revealed that cortical cell types are differentiated by morphological and/or structural variations in distinct subcellular components, namely: the intermacrofibrillar material (IMM), the cytoplasmic remnants (CR), the macrofibrils (Mfs), and the Mf components: the intermediate filaments (IFs) or trichocyte (hard a-keratin) proteins, embedded in a matrix material composed of keratin associated proteins (KAPs).…”
Section: Introductionmentioning
confidence: 88%
“…Hargreaves' preliminary measurements [ 7 ) of the relative hardness of ortho and para components indicate that the para portion is harder than the ortho component by a factor of two. Incieed, the ortho and para cells of mascerated wool fibers have been separated on the l~asis of higher density of the para cells.…”
Section: Mechanical Properties I N Jlue~nce Of Fiber Dianretermentioning
confidence: 99%
“…[28][29][30][31][32] The differing compositions observed in the wool fiber cause spontaneous crimping of the fiber through differential stress relaxation. [29][30][31] Recognition of the mechanism behind the crimping behavior of wool has led to wool-inspired synthetic self-crimping fibers and further to a number of approaches for reversibly crimping fibers, where differential swelling or thermal expansion of the different components were exploited, mostly described in patent literature, [33][34][35][36][37] whereas very few scientific publications on reversibly crimping fibers are available. 38,39 One attractive direction of applications for such fibers has been responsive textiles that are able to reversibly change air permeability.…”
Section: Introductionmentioning
confidence: 99%